2021
DOI: 10.2147/ott.s309917
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Enzalutamide Resistance-Related circRNA-miRNA-mRNA Regulatory Networks in Patients with Prostate Cancer

Abstract: This study aimed to identify enzalutamide resistant-related (EnzR-related) circRNAs and to characterize and validate circRNA-miRNA-mRNA ceRNA regulatory network and corresponding prognostic signature of prostate cancer patients. Methods: We obtained circRNA expression microarray from the Gene Expression Omnibus (GEO) database and performed differential expression analysis to identify EnzR-related circRNAs using the limma package. The miRNA and mRNA expression profiling were downloaded and performed differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The identification of miRNA–mRNA regulatory relationships through a correlation-based approach (i.e., integrating miRNA and mRNA profiling data, finding negative correlations between expression profiles of miRNAs and predicted mRNA targets) has been suggested as a more accurate way to identify critical miRNA–mRNA interactions in PCa [ 214 , 215 , 216 ]. In our previous studies, we combined the correlation-based approach with comprehensive pathway analysis to construct miRNA–mRNA regulatory networks underlying AA PCa disparities.…”
Section: Deregulated Mirnas and Differential Mirna–mrna Regulatory Ne...mentioning
confidence: 99%
“…The identification of miRNA–mRNA regulatory relationships through a correlation-based approach (i.e., integrating miRNA and mRNA profiling data, finding negative correlations between expression profiles of miRNAs and predicted mRNA targets) has been suggested as a more accurate way to identify critical miRNA–mRNA interactions in PCa [ 214 , 215 , 216 ]. In our previous studies, we combined the correlation-based approach with comprehensive pathway analysis to construct miRNA–mRNA regulatory networks underlying AA PCa disparities.…”
Section: Deregulated Mirnas and Differential Mirna–mrna Regulatory Ne...mentioning
confidence: 99%
“…Greene et al screened the circRNA expression of two enzalutamide-resistant LNCaP clones against the control cell line and found 111 commonly altered circRNAs [ 137 ]. Yu et al further analyzedGreene et al’s data and constructed a ceRNA regulatory network [ 138 ]. They chose hsa_circ_0047641 and further validated its effect on the proliferation of enzalutamide-sensitive and resistant PCa cells.…”
Section: Circrnas and Drug Resistance In Pcamentioning
confidence: 99%
“…They could serve as prognostic biomarkers in cancers [ 91 , 108 ]. Some studies, Luo et al [ 108 ] and Yu et al [ 138 ] for example, further illustrated the functions of these circRNAs in cancer invasion and proliferation. However, it should be noted that the effect of these circRNAs on drug resistance was not all experimentally validated, which is mandatory for ascertaining the causal–effect relationship.…”
Section: Limitations and Perspectivesmentioning
confidence: 99%
“…Survival rate analysis in PCa patients by the Kaplan-Meier curve unveiled a positive correlation between higher expression of cognate genes corresponding to anti-carcinogenic circRNAs (hsa_circ_0006410, hsa_circ_AKAP7 and hsa_circ_0005848) and better overall survival (OS) in PCa patients. Also, Yu et al (49) identified 13 circRNAs in association with resistance to enzalutamide as an androgen deprivation therapy (ADP) drug used against PCa. Six miRNAs, 167 mRNAs, and 10 hub genes were identified as targets of the circRNAs.…”
Section: Up-regulated Circrnas In Pcamentioning
confidence: 99%